Alternative educational pathways for higher certificate in information technology graduates at a South African university of technology - Dina Moloja; Moretlo Tlale-Mkhize; Bekithemba Dube (Interdisciplinary Journal of Education Research)
This theoretical paper explores alternative educational pathways for Higher Certificate in Information Technology graduates, addressing the gap between the Higher Certificate in Information Technology qualification and advanced career opportunities. These graduates, who did not meet the minimum requirements for Diploma programmes, often struggle with career advancement due to curriculum mismatches. This limits their ability to pursue advanced qualifications, which are frequently necessary for career growth in the Information Technology industry. The pressing challenge is to identify and develop viable educational pathways that provide these graduates with opportunities for further academic progression or career advancement, addressing gaps in skills, qualifications, and industry requirements. The paper uses the lens of constructivist theory to explore how alternative educational pathways can be designed to support these graduates by promoting active, experiential learning and enabling them to construct knowledge in practical, real-world contexts. We argue that traditional educational pathways are insufficient in addressing the growing needs of students and employers in the Information Technology field. To effectively bridge the gap between certificate-level education and advanced qualifications or employment, the research contends that alternative pathways, such as bridging programmes, work-based learning, and digital education platforms, must be more accessible, better structured, and institutionally supported. This study recommends policy revisions to improve articulation pathways, introduce bridging programmes, and strengthen industry collaboration, promoting lifelong learning through flexible, industry-aligned education for continuous upskilling and enhanced employability in IT.